Motivation of Officers towards the Results of Vessel Sanitation Hygiene Inspections at Class I Quarantine Center (BKK) Banten - Budiman; Lukman Waris; Ismarina (KHD Production, 2024)
The spread of infectious diseases through sea transportation has become a global threat to public health. In this context, the role of the Banten Class I Health Quarantine Center (BKK) is crucial to ensure that ships entering the port area meet cleanliness and sanitation standards. This study explores the motivation of Class I Banten Health Quarantine Center (BKK) officers and the performance of Ship Sanitation Hygiene (HSK) inspection results in the Banten port area. The method used is qualitative. With 12 participants working in BKK Class I. In qualitative research using the